Kandungan Katekin dan Kualitas (Warna Air Seduhan, Flavor, Kenampakan) Enam Klon Teh (Camellia sinensis (L.) O. Kuntze) di Ketinggian yang Berbeda - Suyadi Mitrowihardjo; Woerjono Mangoendidjojo; Hari Hartiko; Prapto Yudono (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2012)
The purpose of the study was to fi nd out high catechins content and quality of six tea clones which might contribute to tea clone improvements in the future. Altitudes growing (1200 – 1300 m above sea level and 700 – 900 m above sea level) which might infl uence the quality were also evaluated. Catechin (C), epicatechin (EC), epigallocatechin (EGC), apicatechin gallate (ECG), epigallocatechin gallate (EGCG) were analysed using high performance liquid chromatography (HPLC) method and tea quality (color, fl avor, appearance) evaluation were performed by three certifi ed tea testers. The results indicated that at higher altitude TRI 2025, PGL 10, and GMB 9 clones showed high total catechins, while at lower altitude PGL 15, GMB 9, and PGL 10 clones showed such high total catechins. Liquor colour scores were not signifi cantly different either between clones or locations, but liquor fl avor scores were found higher on GMB 7 and PGL 15 at either higher or lower altitudes than the rest of the clones evaluated. Liquor flavor scores tend to be better at lower altitude than those at higher altitude. At higher altitude, PGL 15, TRI 2025, GMB 9 performed highest infusion appearance scores, while at lower altitude, TRI 2025 clone showed the highest score. Similar to flavor scores, there was a tendency that the infusion appearance scores were much better at lower altitude than those at higher altitude.ABSTRAKPenelitian bertujuan untuk mendapatkan informasi klon-klon yang dapat memberikan katekin dan kualitas hasil yang tinggi yang diharapkan bermanfaat sebagai arahan perbaikan dalam pengembangan tanaman teh ke depan. Ketinggian tempat tumbuh (1200 – 1300 m dari permukaan laut dan 700 – 900 m dari permukaan laut) yang diduga berpengaruh terhadap kualitas hasil juga dievaluasi, karena terkait dengan ketersediaan lahan pengembangan. Analisis catechin (C), epicatechin (EC), epigallocatechin (EGC), epicatechin gallate (ECG), epigallocatechin gallate (EGCG) dilakukan dengan metode HPLC (High Performance Liquid Chromatography), sedang evaluasi kualitas (warna air seduhan, flavor, kenampakan) dilakukan oleh tiga orang tester teh bersertifi kat. Hasil analisis menunjukkan bahwa total katekin yang tinggi diperlihatkan TRI 2025, PGL 10, GMB 9 di lokasi ketinggian 1200-1300 m dpl, dan total katekin tinggi juga diperlihatkan PGL 15, GMB 9, dan PGL 10 di lokasi ketinggian 700 – 900 m dpl. Skor warna air seduhan tidak menunjukkan perbedaan antar klon maupun antar lokasi, namun skor flavor GMB 7 dan PGL 15 unggul di lokasi atas maupun di lokasi bawah. Ada kecenderungan skor fl avor lebih unggul di lokasi bawah dibanding dengan lokasi atas. Skor kenampakan ampas setelah teh diseduh tinggi untuk PGL 15, TRI 2025, dan GMB 9 di lokasi atas, sedang TRI 2025 tinggi di lokasi bawah. Serupa dengan skor fl avor, skor kenampakan ampas teh berkecenderungan unggul di lokasi bawah.